Electronic circular dichroism spectra using the algebraic diagrammatic construction schemes of the polarization propagator up to third order - Scott, Mikael; Rehn, Dirk R.; Coriani, Sonia; Norman, Patrick; Dreuw, Andreas (The journal of chemical physics, 2021)
Expressions for the calculation of rotatory strengths using the algebraic diagrammatic construction (ADC) scheme of the polarization propagator in both length and velocity gauges have been implemented. This enables the simulation of electronic circular dichroism (ECD) spectra at the ADC level up to third order of perturbation theory. The ADC(n) methods produce rotatory strengths of comparable accuracy to those obtained with coupled cluster methods of corresponding approximation levels, as evaluated for methyloxirane, methylthiirane, dimethyloxirane, dimethylthiirane, hydrogen peroxide, and dihydrogen disulfide. ECD spectra of (1R)-camphor, (1R)-norcamphor, and (1R)-fenchone computed at the third order ADC(3) level of theory are shown to agree very favorably with experimental gas phase spectra, demonstrating the usefulness of ADC for the calculation of chiro-optical properties of organic molecules. ADC(2) in combination with the polarizable continuum model is shown to successfully reproduce the ECD spectrum of the L-epinephrine enantiomer in water, further demonstrating the applicability of this approach.
Gesehen am 22.07.2021